How far to go? Determinants of migration distance in land mammals. (12th April 2015) - Teitelbaum, Claire S.; Fagan, William F.; Fleming, Chris H.; Dressler, Gunnar; Calabrese, Justin M.; Leimgruber, Peter; Mueller, Thomas; Festa‐Bianchet, Marco
Abstract Animal migration is a global phenomenon, but few studies have examined the substantial within‐ and between‐species variation in migration distances. We built a global database of 94 land migrations of large mammalian herbivore populations ranging from 10 to 1638 km. We examined how resource availability, spatial scale of resource variability and body size affect migration distance among populations. Resource availability measured as normalised difference vegetation index had a strong negative effect, predicting a tenfold difference in migration distances between low‐ and high‐resource areas and explaining 23% of the variation in migration distances. We found a weak, positive effect of the spatial scale of resource variability but no effect of body size. Resource‐poor environments are known to increase the size of mammalian home ranges and territories. Here, we demonstrate that for migratory populations as well, animals living in resource‐poor environments travel farther to fulfil their resource needs.